The Inner Conflict and Shadow Self in Estella’s Identity in Cruella (2021): A Jungian Literary Film Analysis - Farah Nurkumaila (Universitas Negeri Surabaya, 2025)
The film Cruella (2021) portrays the main character Estella as she navigates an inner conflict in her quest for identity. This research aims to analyze Estella’s identity struggle and transformation into Cruella through Carl Jung’s theory of the Shadow Self. Using a descriptive qualitative method, this study examines selected scenes and dialogues from the film as primary data. The findings reveal that Estella initially rejects her clever and ambitious side, but later embraces it as an integral part of her identity. This study contributes to a deeper understanding of how accepting one’s shadow can lead to personal power and narrative complexity.